2019
DOI: 10.1016/j.compositesb.2019.107197
|View full text |Cite
|
Sign up to set email alerts
|

Shredding and sieving thermoplastic composite scrap: Method development and analyses of the fibre length distributions

Abstract: A B S T R A C TRecycling of thermoplastic composites has attracted considerable attention in the recent years. Several recycling solutions include shredding scrap to centimetre-sized flakes to retain long fibres, followed by a remanufacturing step that prevents fibre breakage. Determining the exact fibre length distribution (FLD) for these routes is crucial, as it is of importance for the processibility of the material as well as the mechanical performance of the recycled parts. In this paper, novel analysis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Even though they used a different material, different shredders and also a slightly different technique to analyze the fiber length–a similar tendency was observed. Vincent et al 36 found no effect of feedstock size on the particle size and fiber length distribution when shredding a carbon fiber‐reinforced PPS using a two‐shaft shredder. However, it needs to be taken into account, that the shredder was not equipped with a screen, so that the material left the cutting chamber after one cutting step and no particle‐to‐particle‐interaction occured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though they used a different material, different shredders and also a slightly different technique to analyze the fiber length–a similar tendency was observed. Vincent et al 36 found no effect of feedstock size on the particle size and fiber length distribution when shredding a carbon fiber‐reinforced PPS using a two‐shaft shredder. However, it needs to be taken into account, that the shredder was not equipped with a screen, so that the material left the cutting chamber after one cutting step and no particle‐to‐particle‐interaction occured.…”
Section: Resultsmentioning
confidence: 99%
“…The quality of the regrind depends on the plate thickness, especially in relation to the gap width and thus it also depends on the machine design 34 . Another research study dealing with the regrind size and the fiber length after shredding has been published by Vincent et al 36 They investigated the effect of different screen sizes, the rotor number, feedstock size and rotor blade width of the fiber length distribution of PPS with carbon fiber reinforcement using a twin‐shaft and a four‐shaft shredder. To analyze the fiber length of the ground continuous fiber‐reinforced scrap, they used the particle form as well as the orientation of the fiber fabric in the particle.…”
Section: State Of Researchmentioning
confidence: 99%
“…Some batches of shredded flakes were sieved with a multi-stage vibrating sieve. The fibre length distribution (FLD) of the output flakes, as well as the shredding and sieving process, were previously characterised in [10,32] . The FLDs of the categories of flakes used in this study are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, an estimated fibre length reduction in the case of shredded flakes was calculated. The FLD prior to processing was measured from the flakes 29 and is shown in Figure 16 as a solid line. Based on that, each fibre length was assumed to be attrited similarly to the measured 20 mm long fibres (Figure 15), i.e.…”
Section: Fibre Attritionmentioning
confidence: 99%